Topological optimization of continuum structures for additive manufacturing considering thin feature and support structure constraints. Issue 12 (2nd December 2021) - Xu, Bin; Han, Yongsheng; Zhao, Lei; Xie, Yi Min
ABSTRACT: This article proposes a design method to minimize the compliance or maximize the fundamental natural frequency of continuum structures under thin feature and support structure constraints in additive manufacturing processes. The objective functions are, respectively, to minimize the compliance of continuum structures under static loads and maximize the fundamental natural frequency of vibrating continuum structures. The topology optimization is performed by the bi-directional evolutionary structural optimization (BESO) method. The sensitivity expressions for minimizing the compliance or maximizing the fundamental natural frequency are derived in detail. Different thin feature constraints and the support structure constraints in different printing directions are investigated. Several two- and three-dimensional numerical examples involving compliance minimization and eigenfrequency maximization show that the proposed method is effective in achieving convergent solid–void optimized solutions for a variety of optimization problems of continuum structures, and the designs resulting from the new topology optimization algorithm are additive manufacturing friendly.